Inhibition of ornithine decarboxylase potentiates nitric oxide production in LPS-activated J774 cells - Baydoun, Anwar R (1998)
1. We have examined whether modulation of the polyamine biosynthetic pathway, through inhibition by α-difluoromethylornithine (DFMO) of the rate limiting enzyme, ornithine decarboxylase (ODC), modulates NO synthesis in J774 macrophages. 2. DFMO potentiated LPS-stimulated nitrite production in both a concentration- and time-dependent manner, increasing nitrite levels by 48±5% at 10 mM. This effect was observed in cells pre-treated with DFMO for 24 h prior to stimulation with LPS. Addition of DFMO 12 h after LPS failed to potentiate LPS-induced nitrite production. 3. Supplementation of the culture medium with horse serum (10%) in place of foetal calf serum (10%) caused no significant change in either LPS-induced nitrite production or in the ability of DFMO (10  mM) to potentiate LPS-induced NO synthesis. 4. Metabolism of L-[(3)H]arginine to L-[(3)H]citrulline by partially purified inducible nitric oxide synthase (iNOS) was not significantly altered by either DFMO (1–10 mM) or by putrescine (0.001–1 mM), spermidine (0.001–1 mM) or spermine (0.001–1 mM). iNOS activity was also unaffected by 1 mM EGTA but was markedly attenuated (70±0.07%) by L-NMMA (100 μM). 5. Pre-incubation of cells with DFMO (10 mM; 24 h) prior to activation with LPS resulted in enhanced (∼2 fold) iNOS protein expression. 6. These results show that DFMO potentiates LPS-induced nitrite production in the murine macrophage cell line J774. Since the only known mechanism of action of DFMO is inhibition of ODC, and thus polyamine biosynthesis, we conclude that expression of iNOS can be critically regulated by endogenous polyamines.